MDF relaunches journal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'MDF Journal' Management for Development Foundation PO Box 430 - 6710 BK Ede THE NETHERLANDS